Ferroptosis-related gene ATG5 is a novel prognostic biomarker in nasopharyngeal carcinoma and head and neck squamous cell carcinoma - Shi, Ming; Du, Jiangnan; Shi, Jingjing; Huang, Yunchuanxiang; Zhao, Yan; Ma, Lan (Frontiers in Bioengineering and Biotechnology, 2022)
Nasopharyngeal carcinoma (NPC), a subtype of head and neck squamous cell carcinoma (HNSCC), is a malignant tumor that originates in the mucosal epithelium of the nasopharynx. Ferroptosis plays a key role in tumor suppression, while its prognostic value and critical factors in NPC have not been further explored. We select the Cancer Genome Atlas (TCGA) HNSCC dataset and the Gene Expression Omnibus (GEO) dataset of NPC samples, and find that ferroptosis-related factor ATG5 shows a high expression level with poor overall survival (OS) in HNSCC and NPC samples and is positively correlated with PD-L1/PD-L2 expression (p < 0.05). Furthermore, ATG5 high expression HNSCC patients show poor efficacy and short survival after receiving immune checkpoint blockade therapy treatment (p < 0.05). Moreover, ATG5 is significantly positively correlated with G2M checkpoint pathway (ρSpearman = 0.41, p < 0.01), and G2M checkpoint inhibitor drugs have lower IC50 in HNSCC patients with high expression of ATG5 (p < 0.01), indicating the potential value of G2M inhibitors in HNSCC/NPC treatment. In summary, our study shows that ferroptosis-related factors play a key role in immune infiltration in NPC and HNSCC, and ATG5, as a key immune invasion-related ferroptosis-related factor, has the potential to be a novel prognostic biomarker and a potential target in therapy for NPC and HNSCC.